Socio-demographic and clinical characteristics of pregnant and puerperal crack-cocaine using women: preliminary data (Archives of Clinical Psychiatry, 2014)
Background The literature provides several studies on the effects of cocaine when exposed to the fetus. However, the majority of these data comes from animal models. Objective The objective of this study is to present socio-demographic and clinical data in crack-cocaine using pregnant women and their babies, as compared to non-users. Methods Cross-sectional study, comprised by 56 dyads of crack-cocaine using mothers-babies and 89 control dyads. In addition to the socio-demographic data and the babies’ information, data collection was based on ABIPEMI for socioeconomic level, WAIS for IQ, MINI for psychopathology and ASSIST for drug use. Results Most crack users, in comparison to non-users, did not have a partner (10.52% vs 4.4%, P = 0.001) and presented lower IQ (78.15, +/-8.07 vs 84.27 +/- 9.87; P = 0.002). The prevalence of antisocial personality disorder and suicide risk in users was higher than in non-users (24.44% vs none, P < 0.001; 28.26% vs 10.46% P = 0.01). Most of the users did not participate in prenatal care (75%). The babies that the crack-cocaine using mothers gave birth to weighed significantly less than the controls (2.858 g vs 3.240 g, P = 0.002). Discussion Users had a higher degree of psychopathology and lower attendance in prenatal care. There was an overlap of adverse factors, both for exposed mothers and babies. The sum of these vulnerabilities could result in significant harm to the developing infant.